Descriptive Quantitative Analysis of the Agam Maju Generasi Pintar Scholarship Program 2025 in Agam Regency: ANALISIS DESKRIPTIF KUANTITATIF PROGRAM BEASISWA AGAM MAJU GENERASI PINTAR TAHUN 2025 DI KABUPATEN AGAM - Fitri Rahayu; Nelvia Iryani (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2026)
Abstract. This study aims to analyze the implementation of the Agam Maju Generasi Pintar Scholarship Program in 2025 in Agam Regency using a quantitative descriptive approach. The study focuses on the distribution of scholarship recipients, the amount of assistance, and the program’s contribution to improving access to higher education. The data used are secondary data obtained from the Regent’s Decree of Agam Regency in 2025 and publications from the Central Bureau of Statistics. The analysis method employs descriptive statistics in the form of percentages and tabulation. The results show that the total number of recipients is 270 students, dominated by continuing recipients (95.9%), while new recipients account for only 4.1%. The decrease in recipients is influenced by the implementation of DTSEN-based verification. The amount of assistance varies based on the location of the university, indicating a need-based policy approach. Overall, the program contributes to improving access to higher education, although it still functions as supplementary financial support. Abstrak. Penelitian ini bertujuan untuk menganalisis pelaksanaan Program Beasiswa Agam Maju Generasi Pintar Tahun 2025 di Kabupaten Agam dengan menggunakan pendekatan deskriptif kuantitatif. Penelitian ini memfokuskan pada distribusi penerima, besaran bantuan, serta kontribusi program dalam meningkatkan akses pendidikan tinggi. Data yang digunakan merupakan data sekunder yang bersumber dari Keputusan Bupati Agam Tahun 2025 dan publikasi Badan Pusat Statistik. Metode analisis yang digunakan adalah statistik deskriptif berupa persentase dan tabulasi data. Hasil penelitian menunjukkan bahwa jumlah penerima beasiswa sebanyak 270 orang, dengan dominasi penerima lama sebesar 95,9%, sedangkan penerima baru hanya sebesar 4,1%. Penurunan jumlah penerima dipengaruhi oleh penerapan verifikasi berbasis DTSEN. Besaran bantuan yang berbeda berdasarkan lokasi perguruan tinggi menunjukkan adanya kebijakan berbasis kebutuhan. Secara umum, program ini berkontribusi dalam meningkatkan akses pendidikan tinggi, namun masih berfungsi sebagai bantuan tambahan